The Muslim Blog: Current Conversations on Islam from Russian Muslim Women on YouTube - Abdulaev, Sabina; Abdulaev, Narmina (CARAKA : Indonesia Journal of Communication, 2024)
In the Russian Federation, there is a community of 20 million Muslims, making up roughly 13% of the country's population. This demographic presents a diverse minority, characterized by variations in ethnicity, language, and culture. Notably, the case of Russian Muslims stands out due to the significant generational shift observed within the community. Unlike their predecessors, who experienced a disconnect from Islam because of the secularist and communist ideologies prevalent during the Soviet era, the younger generation exhibits a heightened level of religious devotion. This phenomenon underscores the unique dynamic within Russian Muslim society. Central to this discussion are Muslim female YouTubers, who serve as a reliable and easily accessible resource for understanding Islam. Beyond disseminating religious teachings, these content creators utilize the platform to address the challenges confronting Muslims in Russia and the wider Islamic community (ummah). Their presence on YouTube not only facilitates dialogue but also fosters a sense of community among viewers, offering a platform for the exchange of ideas and perspectives.